Toxicidad aguda del extracto hidroetanólico de Tynantus panurensis (clavo huasca) en Mus musculus cepa Balb C - Tenazoa Gomez, Jacob Daniel (2025)
The Amazon forests are a source of bioactive molecules to be discovered, there are some scientific studies and ethnic knowledge of their use; but the toxicological potential of the species is not known. To determine the acute toxicity of the hydroethanolic extract of T. panurensis (huasca clove) in the biological model M. musculus Balb C strain. The study was experimental, which associates the clinical, biochemical and anatomo-histological parameters in the biological model Mus musculus. Balb C strain at doses of 25, 200 and 2000 mg/kg, proposed for the study of plant extracts of roots, bark and leaves. The mortality rate for hydroethanolic extracts of root, bark and leaves at the maximum evaluated dose of 2000 mg/kg m.c. was 0%; the body mass differential during the evaluation period was for root -0.268 to -3.55 g; for bark from 1.94 to -4.66 g and for leaves from -1.25 to 3.5, unlike the control group that showed an increase of 4.9 g. Irritability, passivity, sedation and in some cases increased respiratory frequency or amplitude were observed. And the Glucose parameters for the dose of 2000 mg/kg for the root, bark and leaves exceeded the upper limit 175,600; 180.6 and 160.4 mg/ dL respectively. Some GPT and FA values were also found to be above the range. the dose of 25 mg/kg in the histological sections: 39 normal, 27 with vascular alteration of different degrees and 9 with tissue alteration. In the microscopy of the organs at a dose of 200 mg/kg, 29 normal histological sections were observed, 33 with vascular alteration of different degrees and 13 with tissue alteration. At the dose of 2000 mg/kg, 26 normal histological sections were observed, 36 with vascular alteration of different degrees and 13 with tissue alteration. It was concluded that according to the classification of the toxicity of substances and preparations, the LD50 is above 2000 mg/kg m.c. Therefore the extracts fall into the category of harmless.